Warm Compress on Lowering Body Temperature Among Hyperthermia Patients: A Literature Review - Lilis Lismayanti; Andika Abdul Malik; Nida Siti Padilah; Fidya Anisa Firdaus; Henri Setiawan (International Journal of Nursing and Health Services (IJNHS), 2021)
Hyperthermia increased the core human body temperature above normal 36.7-37.5 °C, usually caused by infection, resulting in fever, and was the most common manifestation. One of the efforts that could be done to overcome the symptoms of hyperthermia was the application of warm compresses to the frontal, axillary, and dorsalis pedis. The study aimed to describe body temperature changes in hyperthermic patients after warm compress was applied. This study used a descriptive design with a literature review approach. Twelve articles were included in this review by six journal databases: PubMed, JSTOR, Wiley Online Library, Sage Journal, Taylor and Francis Online, and Google Scholar. The selection was carried out by assessing articles that met the inclusion criteria, including the publication range for 2008-2021, English and Indonesian languages ??, and open access to full-text pdf. The critical assessment was carried out by using the Critical Appraisal Skills Programmed instrument. The review results showed that the warm compress method had a positive effect in lowering body temperature in the nursing process in patients with hyperthermia. Based on the literature from the reviewed articles, it could be concluded that a warm compress intervention needed to be given to hyperthermic patients to lower the patient's body temperature whether they were undergoing treatment or not